Cyclovirus detection in Chilean adults with and without community‐acquired pneumonia. Issue 8 (2nd June 2021) - Prades, Yara; Pizarro, Rolando; Ruiz, Mauricio; Moreno, Cristian; Avendaño, Luis F.; Luchsinger, Vivian
Abstract: Cycloviruses (CyV) (genus Cyclovirus, family Circoviridae ) are nonenveloped DNA viruses. The first report in humans was in 2010 and research has focused only on disease‐associated human sample detection. The only HuACyV (CyCV‐ChileNPA1, HuACyV10) reported in the Chilean population was in children (3.3%) with an acute respiratory infection. Its detection in respiratory samples from adults, with/without respiratory disease remains unknown. The aim of this study was to detect HuACyV10 in adults with and without respiratory disease. HuACyV10 was studied in nasopharyngeal swabs from 105 hospitalized adults with community‐acquired pneumonia (CAP) and 104 adults without respiratory symptoms. Total nucleic acids were extracted, and viral rep and cp gene fragments were amplified by real‐time polymerase chain reaction. HuACyV10 was detected in 19.05% adults with CAP and in 0.96% asymptomatic adults, being significantly higher in adult CAP than asymptomatic ( n = 1) ones ( p = 0.0001). C t values were between 26.7 and 39.6, and the median was 34.1 for rep and 33.8 for the CAP in adults CAP ( p = 0.68), and 35.7 and 36.0, respectively, in the asymptomatic case. HuACyV10 detection in CAP adults concentrated in the Autumn–Winter season of the Southern hemisphere. The only asymptomatic adult with HuACyV10 was detected in the Spring–Summer period. In this first report of HuACyV10 in respiratory samples from adults, detection was significantly higher in CAP than in asymptomatic adults. As the sensitivity of both rep and cp genes was similar, both can be applied for detecting HuACyV10. It would be advisable to investigate the pathogenic role of HuACyV10 in adult respiratory infections. ​ Highlights: HuACyV10 was detected in respiratory samples from Chilean adults for the first time. HuACyV10 was detected in adults with community‐acquired pneumonia (CAP) in a higher frequency than in asymptomatic adults.